How to Write Religious Ritual into Theatre. Gérard Genette’s Palimpsests Applied in Plautus’ Rudens and Simone Weil’s Venice Sauvée - Ploj, Blaž; Sojer, Thomas (ARYS. Antigüedad: Religiones y Sociedades, 2020)
In theatre, actors often perform religious rituals on stage. In this article, we argue that in some cases, like in Plautus and Simone Weil, religious rituals are not just imitated but the specific performative structure of the ritual enhances the affective charge of the theatre play. To illustrate this technique we apply Gérard Genette’s theory of hypertextuality to develop a new concept of hyper-performativity. Consequently, we analyze Plautus’ Rudens and Simone Weil’s Venise sauvée to portray their hyper-performative techniques, in antiquity as well as in late modernity, how to write religious rituals into theatre.
Keywords: Antiquity and Late Modernity; hyperperformance; performative techniques; Plautus; religious ritual; Simone Weil; theatre